45.9k views
7 votes
Simplify the following expression 5-⁵/2 x 5⁹/2

User JohnRock
by
6.0k points

1 Answer

7 votes

Given:

Consider the given expression is


5^{-(5)/(2)}* 5^{(9)/(2)}

To find:

The simplified form of the given expression.

Solution:

We have,


5^{-(5)/(2)}* 5^{(9)/(2)}

Using properties of exponents, we get


=5^{-(5)/(2)+(9)/(2)}
[\because a^ma^n=a^(m+n)]


=5^{(-5+9)/(2)}


=5^{(4)/(2)}


=5^(2)


=25

Therefore, the simplified form of given expression is 25.

User Andre Albuquerque
by
5.3k points